Bioaccumulation of Heavy and Essential Metals in Trophic Levels of Pond Ecosystem (Journal of Bangladesh Academy of Sciences, 2009)
Bioaccumulation of heavy and essential metals was examined in duckweed (first trophic level) and in a pyralid insect larva (second and successive trophic level) in two different ponds e.g. organic and inorganic ponds. Hospital's waste-materials and inorganic fertilizers were used as duckweed nutrients in organic pond and inorganic pond, respectively. A total of 24 water, duckweed and insect samples were used for analysis of essential and heavy metals. Toxic metals were found to transmit and persist in duckweed. The insect is a duckweed consumer in pond ecosystem. Persistence of heavy metals and essential metals was evidenced in the insect when its larval stages were examined. Nine heavy/essential metals (Pb, Cd, Cu, Co, Mn, Ni, Cr, Fe and Hg) were analyzed by atomic absorption spectrophotometer (AAS). All of these trace metals were greater in evidence in organic pond than the inorganic pond. Some heavy and essential metals did not bio-accumulate from duckweed to insect larval body. Some toxic metals such as Lead, Copper, Manganese and Cobalt were evidenced at high concentration in water, duckweed and insect larvae. The experimental results indicated that persistence of heavy/essential metals occurred in successive trophic levels of pond ecosystem. Key words: Duckweed, pyralid insect, heavy and essential elements, bio-accumulation, pond ecosystem, trophic level DOI: 10.3329/jbas.v33i1.2957 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 131-138, 2009